A novel process for production of spherical PBT powders and their processing behavior during laser beam melting - Schmidt, Jochen; Sachs, Marius; Zhao, Meng; Fanselow, Stephanie; Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar; Wirth, Karl-Ernst; Peukert, Wolfgang (31st International Conference of the POLYMER PROCESSING SOCIETY, 2016)
Additive manufacturing processes like laser beam melting of polymers are established for production of prototypes and individualized parts. The transfer to other areas of application and to serial production is currently hindered by the limited availability of polymer powders with good processability. Within this contribution a novel process route for the production of spherical polymer micron-sized particles of good flowability has been established and applied to produce polybutylene terephthalate (PBT) powders. Moreover, the applicability of the PBT powders in selective laser beam melting and the dependencies of process parameters on device properties will be outlined. First, polymer micro particles are produced by a novel wet grinding method. To improve the flowability the produced particles the particle shape is optimized by rounding in a heated downer reactor. A further improvement of flowability of the cohesive spherical PBT particles is realized by dry coating. An improvement of flowability by a factor of about 5 is achieved by subsequent rounding of the comminution product and dry-coating as proven by tensile strength measurements of the powders. The produced PBT powders were characterized with respect to their processability. Therefore thermal, rheological, optical and bulk properties were analyzed. Based on these investigations a range of processing parameters was derived. Parameter studies on thin layers, produced in a selective laser melting system, were conducted. Hence appropriate parameters for processing the PBT powders by laser beam melting, like building chamber temperature, scan speed and laser power have been identified.
Keywords: downer reactor; dry coating; polybutylene terephthalate (PBT); selective laser beam melting of polymers; wet grinding

Formation of spherical micron-sized polyamide particles for additive manufacturing via liquid-liquid phase separation - Dechet, Maximilian; Kloos, Stephanie; Peukert, Wolfgang; Schmidt, Jochen (AIP Conference Proceedings, 2019)
Selective laser sintering (SLS) is an additive manufacturing (AM) process that yields excellent part qualities with good mechanical properties. The SLS process employs micron-sized polymer particles, which are selectively fused by a laser. While there seem to be hardly any boundaries regarding design, there are quite some restrictions concerning the variety of commercially available SLS materials. With a market share of roughly 90%, polyamide 12 (PA12) is currently the most widely used polymer material for SLS. In order to increase the understanding of the precipitation based manufacturing process for polyamide powders, production of polyamide 11 powders via precipitation in ethanol was investigated. The polymer particles need to be optimized regarding size, shape, flowability and packing characteristics. In this contribution particle manufacturing via liquid-liquid phase separation is discussed. Bulk polymer material of polyamide 11 is directly converted to spherical micron sized particles in a single unit operation. The produced particles are characterized regarding their size and morphology. Furthermore, also structural characteristics, crystallinity and flowability are analyzed and the product properties are correlated with process parameters. We discuss the potential of this process for the production of novel, easy-to-handle polymer particle systems for SLS.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Polymer powder; Precipitation; Selective laser sintering

Generation of multi-material parts with alternating material layers by Simultaneous Laser Beam Melting of polymers - Laumer, Tobias; Stichel, Thomas; Fanselow, Stephanie; Koopmann, Jonas; Amend, Philipp; Schmidt, Michael (International Conference on Additive Technologies - ICAT 2014, 2014)
By using Additive Manufacturing technologies, like Laser Beam Melting (LBM) of polymers, parts can be realized within single days and necessary modifications can be quickly adapted. With increasing complexity, products are often made out of different polymer materials and the need for multi-material parts is an increasing industry requirement, which cannot be fulfilled by the single material parts realizable by LBM. Therefore, Simultaneous Laser Beam Melting (SLBM) as a new Additive Manufacturing technology offers the possibility to build parts consisting of different polymer materials. The realizable parts combine different material properties, like differing stiffness or chemical resistances, within a single part. Up to now, different materials are deposited next to each other on the building platform, thus the boundary surface between the different polymers is orientated perpendicular to the building direction. For this paper, the polymer powders are alternated in building direction. Thus, the boundary surface is orientated horizontally and is larger, both influencing the boundary surface and resulting part properties, which are analyzed by a high-resolution thermal imaging system and by cross sections.
Keywords: Additive Manufacturing; Simultaneous Laser Beam Melting; Multi-Material Parts

Herstellung und Funktionalisierung neuartiger Pulverwerkstoffe für die additive Fertigung - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)

Herstellung von Polyolefinstrahlschmelzmaterialien mittels Schmelzeemulgieren zum Einsatz in der additiven Fertigung - Schmidt, Jochen; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang; Hiller, Saskia; Laumer, Tobias; Schmidt, Michael (Neue Entwicklungen in der Additiven Fertigung, 2015)
Im Rahmen dieses Beitrags wird das Schmelzeemulgieren als Verfahren zur Herstel-lung von Polymermikropartikeln vorgestellt. In diesem Prozess wird zunächst ein Polymergranulat in einer kontinuierlichen Phase in Gegenwart geeigneter Additive in einem Rührbehälter aufgeschmolzen, die Rohemulsion in einer Rotor-Stator-Einheit feinemulgiert und anschließend zu einer Suspension abgekühlt. Der Einfluss von Prozessparametern und Systemzusam-mensetzung auf das Emulgierergebnis wird diskutiert und die Anwendbarkeit des Verfahrens für polymere Mikropartikeln anhand von Polypropylen (PP) und Polyethylen (PE-HD) dargestellt. Die erhaltenen Suspensionen werden zur Überführung in Pulverform sprühgetrocknet und die Fließeigenschaften des Pulvers analysiert. Durch trockenes Beschichten mit pyrogener Kieselsäure kann die Fließfähigkeit der erhaltenen Partikeln weiter verbessert werden. Das Verfahren bietet somit einen neuen Zugang zur Herstellung neuer Ausgangsmaterialien für die Additive Fertigung.<br

New approaches towards production of polymer powders for selective laser beam melting of polymers - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (32nd International Conference of the Polymer Processing Society, PPS 2016, 2017)
Keywords: wet grinding; dry coating; downer reactor; melt emulsification; laser beam melting of polymers; polypropylene (PP); polybutylene terephthalate (PBT)

New approach towards production of optimized polymer powders for additive manufacturing - Peukert, Wolfgang; Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst (8th International Conference for Conveying and Handling of Particulate Solids (CHoPS2015), 2015)
Rapid prototyping gradually is transferred to additive manufacturing opening many new applications. Especially powder- And beam-based processes such as laser beam melting (LBM) of polymers are promising. Major requirements for good processability in LBM of polymers are good flowability and high packing density. Within this contribution a novel process route for the production of micron-sized LBM powders [1] is presented exemplarily for polybutylene terephthalate (PBT). Wet comminution of the polymer is the first process step. Product particles with x < 10 μm are readily obtained by wet grinding [2]. The ground PBT microparticles are rounded in a heated downer reactor in the second process step. To increase the flowability of the spherical polymer particles further nanoparticles are adhered to the particle surface [3] in the third step. Spherical PBT microparticles of good flowability are obtained.
Keywords: powder; polymer; laser; beam; melting

Novel approaches for the production of polymer powders for selective laser beam melting of polymers - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (Solid Freeform Fabrication 2016: Proceedings of the 26th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference, 2016)
The opening of new fields of application of powder-based additive manufacturing methods like selective laser beam melting of polymers currently is hindered by the limited availability of materials showing good processability. So far, virtually only polyamides are available as optimized powder materials. Two innovative methods for production of spherical polymer micro particles for selective laser melting are discussed: The first approach, stirred media milling and rounding, is applicable for a variety of polymers. It will be exemplarily discussed for polyesters and the dependency of product properties (particle size distribution, shape, crystallinity) on the process parameters in the comminution and in the rounding step will be assessed. The second method, melt emulsification, will be demonstrated for polypropylene. Moreover, the possibilities of dry coating to tailor particle properties are illustrated. The influence of powder properties on the processability and on the quality of the obtained devices is outlined.<br
Keywords: AdditivesCrystallinityEmulsificationLaser beamsMeltingParticle sizeParticle size analysisPolypropylenes Selective Laser Sintering; Nylon 12; Polybutylene Terephthalate; Innovative method; Laser beam melting; Particle properties; Polymer powders; Powder properties; Process parameters; Product property; Spherical polymers; Selective laser melting

Novel process routes towards the production of spherical polymer powders for selective laser sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Kloos, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (AIP Conference Proceedings, 2019)
Additive manufacturing processes allow the production of individualized and complex parts without the use of molds or tools. Especially powder and beam-based AM processes like selective laser sintering (SLS) of polymers are promising, although the choice of commercial SLS powders is very limited. To further extend the applications of SLS, new and cheap materials with good processability must be supplied. Within this contribution two innovative methods for production of spherical polymer micro particles for SLS are discussed: The first approach is a process chain applicable to a wide range of polymers consisting of wet grinding in a stirred media mill followed by rounding of the obtained irregularshaped particles in a heated downer reactor and subsequent dry coating of the spherical particles for improvement of powder flowability. It will be outlined for glass-filled PBT systems. The second approach is melt emulsification with subsequent dry coating. In this process a polymer melt is emulsified by elongational and shear stresses in a rotor stator device. The method is exemplified for polypropylene (PP). Both approaches allow for production of spherical polymer micro particles. The effect of flowability, shape and bulk density on the powders' processabilities in SLS is assessed.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Melt emulsification; Polymer powder; Rounding

Optimized polybutylene terephthalate powders for selective laser beam melting - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Zhao, Meng; Romeis, Stefan; Drummer, Dietmar; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemical Engineering Science, 2016)
Additive manufacturing processes like selective laser beam melting of polymers (LBM) are established for production of prototypes and individualized parts. The transfer to serial production currently is hindered by the limited availability of polymer powders with good processability. Within this contribution the effect of powder properties, such as particle size, shape and flowability on the processability in LBM and their influence on device quality is exemplified for polybutylene terephthalate (PBT) materials. A process chain for the production of spherical polymer microparticles has been developed to obtain PBT powder materials. The process chain consists of three steps: first, polymer microparticles are produced by wet grinding. Second, the particle shape is engineered by rounding in a heated downer reactor to improve the flowability of the product. Third, a further improvement of flowability of the still cohesive spherical PBT particles is realized by dry coating with fumed silica. Moreover, properties of the PBT powders obtained along the process chain are thoroughly characterized with respect to structure and crystallinity by infrared spectroscopy, X-ray diffraction and differential scanning calorimetry. The effect of flowability, shape and bulk density on the powders’ processabilities in LBM is assessed by characterization of the quality of thin layers built in a LBM device. It is demonstrated that the device quality is strongly determined by particle properties: powders of good flowability and high bulk density are mandatory to obtain dense devices.
Keywords: Downer reactor; Dry particle coating; Flowability; Poly butylene terephthalate; Selective laser beam melting; Wet grinding

Production of Micron-Sized particles by melt emulsification - Fanselow, Stephanie; Schmidt, Jochen; Wirth, Karl-Ernst; Peukert, Wolfgang (8th International Conference for Conveying and Handling of Particulate Solids, CHoPS 2015, 2015)
Melt emulsification permits the production of spherical particles and is well-known for pharmaceutical applications and in the food industries. To increase the spectrum of applications the feasibility of the process for polymers is presented. In this study the influence of process parameters such as rotor-stator speed, temperature and dispersed phase viscosity on the particle size distribution of paraffin and polyethylene (PE) wax will be discussed. A major challenge is the stabilization of the droplet interface, thus, a new method for the selection of an efficient emulsifier using a high-pressure/high-temperature cell will be presented. Finally, results for higher viscous technical polymers, such as polypropylene (PP) will be presented. PP is a promising candidate for advanced powders to be used in additive manufacturing processes like laser beam melting (LBM) of polymers, i.e. melt emulsification might be a suitable approach to produce new and optimized LBM powder
Keywords: Laser beams; Particle size; Particle size analysis; Polymers; Polypropylenes; Powders; Additive manufacturing process; Dispersed phase; Food industries; Influence of process parameters; Laser beam melting; Micron-sized particles; Pharmaceutical applications; Spherical particle; Emulsification

Production of micron-sized polymer particles for additive manufacturing by melt emulsification - Peukert, Wolfgang; Fanselow, Stephanie; Schmidt, Jochen; Wirth, Karl-Ernst (Proceedings of PPS-31, 2016)
Melt emulsification is an advanced top-down approach that permits to produce spherical particles and thus widens the availability of polymer feed materials for additive manufacturing. In the process the polymer is molten in a continuous phase and droplet breakup is realized in a rotor-stator-device. The stabilization of the newly formed surfaces is quite challenging. Therefore, a new method to identify an appropriate emulsifier by measuring the interfacial tension between the polymer and continuous phase using a high pressure / high temperature cell is presented. The obtained powders are characterized by scanning electron microscopy (SEM) and by a Zimmermann tensile strength tester to determine the powder flowability. The processability of the polymer powders for additive manufacturing is investigated and demonstrated by building single layers by laser beam melting.
Keywords: additive manufacturing; melt emulsification; polymers

Production of Spherical Micron-Sized Polymer Particles for Additive Manufacturing by Liquid Phase Processes - Dechet, Maximilian; Kloos, Stephanie; Peukert, Wolfgang; Schmidt, Jochen (Proceedings of the Europe/Africa Conference Dresden 2017 Polymer Processing Society PPS, 2019)
CRIS-Team WoS Importer:2019-05-03

Production of spherical semi-crystalline polycarbonate microparticles for Additive Manufacturing by liquid-liquid phase separation - Kloos, Stephanie; Dechet, Maximilian; Peukert, Wolfgang; Schmidt, Jochen (Powder Technology, 2018)
Keywords: Polycarbonate (PC); Polymer microspheres; Additive Manufacturing (AM); Semi-crystalline thermoplast; Thermally induced phase separation (TIPS)

Production of spherical wax and polyolefin microparticles by melt emulsification for additive manufacturing - Fanselow, Stephanie; Emamjomeh, S. Ehsan; Wirth, Karl-Ernst; Schmidt, Jochen; Peukert, Wolfgang (Chemical Engineering Science, 2016)
Keywords: Melt emulsification; Polymer microspheres; Waxes; Polyethylene (PE); Polypropylene (PP); Additive manufacturing